Does Taxation Stifle Corporate Investment? : Firm-Level Evidence from ASEAN Countries - Cevik, Serhan (IMF Working Papers; Working Paper ;, 2018)
This paper conducts a firm-level analysis of the effect of taxation on corporate investment patterns in member states of the Association of Southeast Asian Nations (ASEAN). Using large-scale panel data on nonfinancial firms over the period 1990-2014, and controlling for macro-structural differences among countries, we find a significant degree of persistence in firms' net fixed investments over time, which vary with firm characteristics, such as size, sales, profitability, leverage, and age. Our analysis brings up interesting empirical results, including nonlinear patterns of behavior in firms' capital investment decisions acrosss ASEAN countries. Concerning the main variable of interest, we find that a moderate level of taxation does not hinder business investment, but this effect turns negative as higher tax burden raises the user cost of capital and distorts resource allocations.